Comorbidities of early-onset temporal epilepsy: Cognitive, social, emotional, and morphologic dimensions - Mikulecká, Anna; Druga, Rastislav; Stuchlík, Aleš; Mareš, Pavel; Kubová, Hana (Experimental neurology, 2019)
Epilepsy, the most common neurologic disorder in childhood, is associated with a subset of psychiatric dysfunctions, including cognitive deficits, and alterations in emotionality (e.g., anxiety and depression) and social functioning. In the present study, we evaluated an integrative set of behavioral responses, including cognitive/socio-cognitive and emotional dimensions, using a number of behavioral paradigms in the LiCl/pilocarpine model of status epilepticus (SE) in rats. The aims of the study were to examine whether SE affects: 1) non-associative learning (habituation of exploratory behavior); 2) investigatory response to an indifferent stimulus object; 3) sociability/social novelty preference; 4) social recognition or discrimination; and 4) short- and long-term memory in the Morris water maze (MWM). Finally, we investigated the morphology of key brain structures involved in the examined behavioral dysfunctions. SE did not affect habituation to an open-field arena in juvenile (P25), adolescent (P32), or adult (P80) rats. SE rats spent less time in the central part of the arena. SE adolescent rats (P32) displayed a higher number of rearings with a shorter duration. SE rats displayed a markedly attenuated investigatory response to an indifferent stimulus object. SE rats in all age groups demonstrated pronounced deficits in sociability and the preference for social novelty. In addition, SE rats spent a reduced amount of time investigating a juvenile rat upon first exposure. After 30 min re-exposure together with an additional, novel juvenile, the SE rats spent equal time investigating both juveniles. In the MWM task, acquisition was unimpaired but there was a deficit in delayed memory retention after 10 days. SE did not affect cognitive flexibility expressed by reversal learning. Together, these findings suggest that early-life SE leads to alterations in emotional/anxiety-related behavior and affects sociability/preference for social novelty and social discrimination. Early-life SE did not alter acquisition of spatial learning, but it impaired delayed retention. Using Fluoro Jade B staining performed 24 h after SE revealed apparent neurodegeneration in the dorsal hippocampus, mediodorsal thalamic nucleus and medial amygdala, brain areas that are critically involved in network underlying emotional behavior and cognitive functions.
Keywords: Behavior, Animal; Male; kognitivní poruchy; Rats, Wistar; Brain; Maze Learning; mužské pohlaví; Status epilepticus; potkani Wistar; Spatial learning; krysa rodu Rattus; bludiště - učení; Hippocampus; Pilocarpine; Animals; zvířata; Cognition Disorders; Rats; mozek; chování zvířat; Epilepsy, Temporal Lobe; Exploratory behavior; Epilepsy; Depression; epilepsie temporálního laloku; Anxiety; Cognition